Evaluation and Management of Atherosclerotic Carotid Stenosis - Meschia, James F. (Mayo Clin Proc, 2017)
Medical therapies for the prevention of stroke have advanced considerably in the last several years. There can also be a role for mechanical restoration of the lumen by endarterectomy or stenting in selected patients with high-grade atherosclerotic stenosis of the extracranial carotid artery. Endarterectomy is generally recommended for patients with high-grade symptomatic carotid stenosis. Stenting is considered an option for patients at high risk of complications with endarterectomy. Whether revascularization is better than contemporary medical therapy for asymptomatic extracranial carotid stenosis is a subject of several ongoing randomized clinical trials in the United States and internationally.